An Evaluation of Student Implemented Clean Water Programs in Ecuador. - String, Gabrielle. (2017)
Abstract: Engineers Without Borders (EWB-USA) is a non-profit, non-competitive, humanitarian organization established to partner with developing communities worldwide in order to improve their quality of life, while training internationally responsible professionals and students. This research evaluates case study Programs completed by two student EWB-USA Chapters in Ecuador; to inform about monitoring and evaluation which currently receives minimal support from the EWB-USA Project Process. Project sites were visited for an evaluation, at which point, water quality testing, household surveys, and key informant interviews were conducted. Although the Programs varied by community, goals, project type, implementation strategy, and evaluative metrics, a common narrative was found between the student Programs. These commonalities were used to develop recommendations on the Project process such as identification of measurable metrics, enhancement of the EWB-USA Technical Advisory Committee, creation of an open source network for intra-Chapter knowledge sharing, and creation of an online file-sharing and database for Programs.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Douglas Matson.; Committee: Daniel Hannon, Daniele Lantagne, and Shane Rogers.; Keywords: Mechanical engineering, and Environmental engineering.